Chicken Feather Fibres As An Adsorbent In Treating Heavy Metal - Nizam, Ahmad Nikmall Syharifuddin Ahmad (Universiti Sains Malaysia, 2019)
The chicken feather which is a waste product from poultry farm in wastewater treatment has attracts interest from many researchers. This study only focussed on chicken feather fibres as an adsorbent which was prepared by chemical treatment for the removal of heavy metal from the synthetic wastewater. In the purpose of improving the adsorption capacity of Manganese (Mn) and Zinc (Zn), the preparation of chemically modified chicken feather (CMCFs) was done by several methods. First, the chicken feathers were modified and treated with aqueous NaOH solution at different concentrations. This is to clarify the changes in the structure and morphology of chicken feathers (CFs). Next, the dissolved keratin fragments could be rejoined back to the CFs surface by the cross-linking reaction with Epichlorohydrin (Epi) in aqueous NaOH solution, which will be named as Epi/CF adsorbent, and lastly CFs were functionalized with Ethylenediamine (EA) in aqueous NaOH solution by Epi cross-links. The characterization was done using different methods which is SEM-EDX, BET and FTIR. SEM-EDX was done to investigate the structure and properties of CMCFs. NaOH-treated CFs at different concentration were found to be similar in structure and properties to each other while Epi/CF and EAEpi/CF shows significant differences. BET was done to determine surface pore size of CMCFs. The elemental analysis of the chicken feathers was done by FTIR. NaOH-treated CFs have been observed to have better adsorption capacities compared to Epi/CF and EAEpi/CF adsorbents during the removal of heavy metals.. Hence, for both removals of heavy metals, NaOH-0.2/CF has been chosen as the best adsorbent with removal capabilities of 100% for both Mn and Zn. Thus, the result obtained from the optimization study done by using NaOH-0.2/CF as the best adsorbent, at the optimum condition; 0.50 g mass of adsorbent, 23.64 hrs contact time and at the concentration of heavy metals which is 5.33 mg/l shows that the predicted model is valid to be applied in the actual system as for both heavy metals, the error and standard deviation calculated is below 1. The equilibrium adsorption isotherm for the CMCFs mostly fit the Langmuir model for the removal of Mn (R2 ≈ 0.9) while for the Zn removal (R2 ≈ 0.8), the adsorption process follows Freundlich. This means that the adsorption process of Mn using CMCFs is chemisorptions and that for Zn is physisorptions Overall, this study proved that the modified CF has a good potential to be used as an adsorbent to remove the heavy metal.